Distribution of Liquid Mass in Transient Sprays Measured Using Laser-Plasma-Driven X-Ray Tomography - Guenot, Diego; Svendsen, Kristoffer; Lehnert, Bastian; Ulrich, Hannah; Persson, Anders; Permogorov, Alexander; Zigan, Lars; Wensing, Michael; Lundh, Olle; Berrocal, Edouard (Physical Review Applied, 2022)
We report, the use of laser-plasma-driven x rays to reveal the three-dimensional (3D) structure of a highly atomizing water spray. Soft x rays approximately 5 keV are generated by means of a laser-plasma accelerator. Transmission radiography measurements are performed at different angles, by rotating a multihole injector. Using computer tomography, the local liquid volume distribution and its spatial variation are retrieved in 3D, showing up to 55% liquid fraction at the nozzle outlet, which decreases to below 7% within only 1 mm. The resolution of the liquid volume fraction is 0.5% while the spatial resolution of the radiographic images is 11.5μm. The x-ray source used here provides successful measurements of liquid mass distribution over a relatively large volume and is very promising for the analysis of a variety of challenging transient spray systems, e.g., the injection of liquid synthetic and biofuels used for future clean-combustion applications.
CRIS-Team Scopus Importer:2022-07-22